Stimulation of Pressure on Liquid Concept in Stad Learning Model to Improve Rational Thinking Skills and Learning Outcomes of Students (Jurnal Pendidikan Fisika Indonesia, 2018)
The research aims to determine the effect of using cooperative learning model type STAD on learning science to students’ performance in rational thinking skills and learning outcome. The point of view of this influence is seen from the presence or absence of improvement rational thinking skills activity of cognitive learning outcomes after treatment. The research used experimental method with the design One Shot Case Study and took place in SMPN 3 Gorontalo. The data obtained were students’ performance in rational thinking skill and learning outcome gathered by observation sheet of students’ activity and test sheet. The result show that increase in average score of students’ performance in rational thinking in the third meeting compared to the first meeting by indicators of information digging, information processing, problem solving, and conclusion formulating. The overall result shows that the students’ performance in rational thinking skills achieves good criteria; additionally, the students’ learning outcomes achieve average score of 83.81, categorized as B (good).Penelitian ini bertujuan melihat pengaruh penggunaan model kooperatif tipe STAD pada pembelajaran IPA terhadap kecakapan berfikir rasional dan hasil belajar kognitif siswa. Pengaruh ini dilihat dari ada atau tidaknya peningkatan aktivitas kecakapan berfikir rasional dan hasil belajar kognitif siswa setelah diberikan perlakuan. Penelitian ini menggunakan metode eksperimen dengan desain One Shot Case Study yang dilaksanakan di SMP Negeri 3 Gorontalo. Data yang diperoleh berupa aktivitas kecakapan berfikir rasional siswa dan hasil belajar kognitif yang dijaring dengan menggunakan lembar pengamatan aktivitas siswa dan lembar tes. Hasil yang diperoleh menunjukkan terjadi peningkatan rerata skor aktivitas siswa untuk kecakapan berfikir rasional pada pertemuan ketiga bila dibandingkan dengan pertemuan pertama untuk masing-masing indikator menggali informasi, mengolah informasi, memecahkan masalah dan membuat kesimpulan. Hasil penelitian secara keseluruhan menunjukkan perolehan dengan kriteria sangat baik untuk kecakapan berfikir rasional siswa, dan untuk hasil belajar kognitif siswa diperoleh rerata skor sebesar 83.81 dengan predikat B (baik).